Increased long-term mortality in patients with type 2 myocardial infarction, data from the ECAD registry. (14th October 2021) - Hinrichs, L; Hendricks, S; Dykun, I; Rassaf, T; Mahabadi, A A; Totzeck, M
Abstract: Background: The characterization of five different clinical types of acute myocardial infarction (MI) was recently updated in 2018. Type 1 MI is caused by plaque rupture leading to an acute atherothrombotic coronary event. Type 2 MI is an entity where a condition other than coronary artery disease leads to a critical imbalance between oxygen supply and demand. There exist controversial data about the prognosis of patients with type 2 MI. While some studies have shown that type 2 MI is associated with higher mortality rates compared to type 1 MI, other trials revealed comparable mortality rates after multivariate adjustment. Purpose: The aim of the present study was to compare the mortality rates of patients without MI with patients, which presented with type 1 and type 2 MI. Methods: The present analysis is a longitudinal registry analysis based on the Essen Registry of Coronary Artery Disease (ECAD registry) of patients undergoing coronary angiography at the West German Heart and Vascular Center, Department of Cardiology and Vascular Medicine, at the University Hospital Essen between 2004 and 2019. Type 1 MI was defined as a significant increased troponin level (Siemens Troponin I (Dimension) >0, 1 ng/ml and Troponin I Ultra (Centaur) >40 ng/l) and coronary stenosis requiring intervention. Type 2 MI was defined as a significant troponin increase without percutaneous coronary intervention. During follow up, the all-cause mortality of patients without MI and patients with type 1 and 2 MI was investigated. Cox regression analysis was used to determine the association of type 1 and 2 MI with all-cause mortality. Multivariable adjustment was performed for age, sex, low-density lipoprotein cholesterol, systolic blood pressure, diabetes, family history of coronary artery disease and nicotine abuse. Results: Overall, data from 18, 286 coronary angiography exams (mean age 65.3±13.0 years, 71.6% male) were included in our analysis. 14, 883 patients (81.3%) had no MI, 1, 699 patients (9.3%) presented with type 1 MI and 1, 704 patients (9.3%) presented with type 2 MI. During a mean follow-up of 3.4±3.6 years, 3321 deaths occurred (18.2%). Compared to patients without MI (16.1%), patients with type 1 MI (25.2%) and type 2 MI (29.1%) had significant higher mortality rates (p= <0.0001). In Cox unadjusted and multivariable adjusted regression analysis, Type 1 MI (Hazard ratio [standard deviation]: 1.42 [1.14–1.76], p=0.0015) and type 2 MI (2.326 [1.91–2.84], p= <0.0001) were significantly associated with an increased all-cause mortality compared to patients without MI. Kaplan-Meier analysis confirmed the lowest survival rates for patients with type 2 MI (Figure 1). Conclusion: In this large longitudinal registry cohort of patients undergoing invasive coronary angiography, type 2 MI was associated with impaired long-term survival. Prospective studies are required to determine risk stratification for these high-risk populations. FUNDunding Acknowledgement: Type of funding sources: None.